2013
DOI: 10.1021/nl400827p
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Electrical Properties of Graphene by Substrate-Induced Nanomodulation

Abstract: A periodically modulated graphene (PMG) generated by nanopatterned surfaces is reported to profoundly modify the intrinsic electronic properties of graphene. The temperature dependence of the sheet resistivity and gate response measurements clearly show a semiconductor-like behavior. Raman spectroscopy reveals significant shifts of the G and the 2D modes induced by the interaction with the underlying grid-like nanostructure. The influence of the periodic, alternating contact with the substrate surface was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
94
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 35 publications
4
94
0
2
Order By: Relevance
“…When considering utilizing graphene in real devices however, it must be recognized that its electronic and mechanical properties strongly depend on the interfacial interaction with the underlying substrate [24,25]. Due to its high out-of-plane flexibility, the morphology of graphene is dictated by the substrate geometry, which influences the measured properties through changes in electronic structure, topological defects, and chemical doping effects [26][27][28][29][30][31], and the frictional properties of graphene have been reported to have a unique dependence on the substrate surface roughness and interfacial adhesion [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…When considering utilizing graphene in real devices however, it must be recognized that its electronic and mechanical properties strongly depend on the interfacial interaction with the underlying substrate [24,25]. Due to its high out-of-plane flexibility, the morphology of graphene is dictated by the substrate geometry, which influences the measured properties through changes in electronic structure, topological defects, and chemical doping effects [26][27][28][29][30][31], and the frictional properties of graphene have been reported to have a unique dependence on the substrate surface roughness and interfacial adhesion [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…26 Our study combines strategies (i) to (iii) and expands the available intercalation strategies by use of molecular intercalants. Intercalation is a wellknown method to achieve charge doping in layered van-der-Waals bonded materials such as graphite or h-BN.…”
mentioning
confidence: 99%
“…There are several recent studies which investigate the effects of substrate induced geometrical modulations on the electronic and transport properties of graphene. [7][8][9][10] In particular, Low and coworkers 9 considered the effect on the electronic transport when graphene is deformed due to physisorption on a flat substrate presenting an abrupt step. They used a simple Lennard-Jones potential to model the substrate-graphene interaction with parameters corresponding to a step in SiC, and found that the bend itself causes an insignificant scattering of the electrons.…”
mentioning
confidence: 99%